2021
DOI: 10.3389/fpsyg.2021.726072
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Processes Influencing Mental Health Among Winter Sports Athletes in China

Abstract: This study examined the association between motivational processes, psychological distress (depression, anxiety, and stress), and burnout among winter sports athletes within the Hierarchical Model of Intrinsic and Extrinsic Motivation (HMIEM). A total of 685 winter sport athletes participated in this study (377 males, 308 females, age range 18–25 years), from three sport universities across nine winter sports. They completed five psychometric inventories related to motivational factors and mental disorders. Ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Last, the bias statistics suggested that this relationship requires many studies for the relationship to change, confirming a fairly robust relationship. Figure references [24,41,42,44,46,48,49,51,53,56,57,60,61,63,64,[69][70][71]78,80,81,84,86,93,94,96,98,[101][102][103]107,109,112,116,117,120].…”
Section: Meta Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Last, the bias statistics suggested that this relationship requires many studies for the relationship to change, confirming a fairly robust relationship. Figure references [24,41,42,44,46,48,49,51,53,56,57,60,61,63,64,[69][70][71]78,80,81,84,86,93,94,96,98,[101][102][103]107,109,112,116,117,120].…”
Section: Meta Analysismentioning
confidence: 99%
“…Ego climate and negative affect statistics expressed as correlations (r) with corresponding forest plots. Figure references [24,41,42,44,46,48,49,51,53,56,57,60,61,63,64,[69][70][71]78,80,81,84,86,93,94,96,98,[101][102][103]107,109,112,116,117,120].…”
Section: Study Namementioning
confidence: 99%